Knowledge, Attitude & Practice regarding use of Personal Protective Equipment (PPE) among Dental Assistants Working at Tertiary Care Hospitals of Multan, Pakistan - Javaid, Mohsin; Kumar, Ramesh; Abbasi, Mudassar Mushtaq Jawad; Kiyani, Shoaib; ., Kavita; Basharat, Saadia (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To determine knowledge, attitude, practice of using Personal Protective Equipment (PPE) among dental assistants working at tertiary care hospitals of Multan. METHODOLOY: Descriptive cross-sectional study was conducted in Multan by completing 98 questionnaires through random sampling technique from private and public sector hospital. Data was analyzed with SPSS, with the significant level being p<0.05 by using chia-square test. RESULTS: Majority 50 (51.02) participants were from private hospitals and 26 (52%) participants from private sector have a good knowledge about the use of PPE where as 34(70.8%) participants from the public sector had good knowledge as compare to private hospital. 34 (68%) participants from the private sector has a good or positive attitude towards the use of PPE as compared to 36 (75%) participants from the public sector. 29 (58%) participants from the private sector use PPE as compared to 31 (65%) participants from the public sector. P-value for knowledge vs practice of public sector was 0.046 (p<0.05), which was statistically significant and p-value for attitude vs practice of public sector was 0.015 (p<0.05), which was also statistically significant. However, in private sector hospitals we did not find any statistical significance. CONCLUSION: Study has concluded that the Knowledge, Attitude & Practice among dental assistants working in Public sector was better than those who were working in private sector hospitals.